2018
DOI: 10.11114/jets.v6i2.2680
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leisure Participation on Social Adaptation of International Students

Abstract: International students, often a noteworthy group, constitute about 10 per cent of the student population on many campuses throughout the world (OECD, 2009). At any time, there are likely to be over a million students and scholars attending institutions of higher learning abroad, and recent estimates have set the figure at about 4.5 million (Çetinsaya, G.2014). A significant portion of the contemporary literature has dealt with the problems of international students. Owing to the importance of international st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
1
9
0
Order By: Relevance
“…Literature on leisure studies suggests that leisure activity can serve as an effective coping strategy to deal with adaptation challenges (J. Kim, 2012 ). Prior studies have indicated that participating in leisure helped international students to gain cultural knowledge and effectively embrace new cultural values and perspectives (Lee et al, 2018 ; Zerengok et al, 2018 ). International students have used leisure as a way of connecting with host individuals, reducing stress, and adjusting socially, resulting in better mental health and overall quality of life.…”
mentioning
confidence: 99%
“…Literature on leisure studies suggests that leisure activity can serve as an effective coping strategy to deal with adaptation challenges (J. Kim, 2012 ). Prior studies have indicated that participating in leisure helped international students to gain cultural knowledge and effectively embrace new cultural values and perspectives (Lee et al, 2018 ; Zerengok et al, 2018 ). International students have used leisure as a way of connecting with host individuals, reducing stress, and adjusting socially, resulting in better mental health and overall quality of life.…”
mentioning
confidence: 99%
“…Foreign females with an active motor position are significantly ahead of their peers in functional characteristics [1]. Only the implementation of a systematic educational and extracurricular physical education and recreational activities can enhance the effect of positive social and psychological adaptation of foreign students in higher education [4]. Therefore, our study does not contradict these trends.…”
Section: Discussionmentioning
confidence: 68%
“…The quality of Russian higher education and the conditions of study correspond to the needs of foreign prospective students [3]. Problems of foreign students' adaptation to the study process are an important element in the vocational training system [4].…”
Section: Introductionmentioning
confidence: 99%
“…The alumni built better relationships, especially outside school. Leisure time activities impact not only the social adjustment of the students but also psychological and physiological benefits (Zerengok et al, 2018). It also had a positive effect on their emotional and mental well-being.…”
Section: B Social Adaptationsmentioning
confidence: 99%
“…First, the alumni eased themselves by socializing and searching for hobbies. Zerengok et al (2018) imply that leisure participation is a promising tool to create socially accommodating environments for this population." Socializing relieves culture shock, considering that the alumni meet new people in a foreign country.…”
Section: B Social Adaptationsmentioning
confidence: 99%